A cross-national perspective on the associations of grit with career success. Issue 2 (17th February 2020) - Danner, Daniel; Lechner, Clemens M.; Rammstedt, Beatrice
ABSTRACT: This paper presents one of the first cross-nationally comparative studies on the economic and social returns to grit (perseverance and passion for long-term goals). Specifically, we investigated whether grit incrementally predicted objective (income) and subjective (job satisfaction) career success over and above cognitive skills and educational attainment; whether grit's association with career success was moderated by individual characteristics; whether grit's associations with career success varied across countries; and whether this variation could be explained by labour market conditions (unemployment rates). Multi-group structural equation models with data from 6, 738 respondents from 19 countries revealed that grit was incrementally associated with income and job satisfaction in some but not all countries. Grit's effect sizes were mostly modest, yet there were some indications for variations by education and labour market conditions. Overall, these findings suggest that the associations between grit and career success are not uniform but vary across individuals and contexts.